Structural Constraints and Adaptive Budgeting Practices in Private School Financial Management: A Qualitative Case Study of BOS Dependent Educational Financing in Indonesia - Shihab Solahudin; Hinggil Permana; Fatimah Az Zahro (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Effective budgeting is widely recognized as a determinant of educational quality in resource-constrained school systems, yet empirical research on the operational mechanisms through which Indonesian private schools manage budgeting under structural financial limitations remains limited. This study examined the budgeting management of educational financing at SMP Krida Mandiri, a private junior secondary school in Bekasi Regency, West Java, Indonesia, with particular attention to the three sequential budgeting phases of planning, implementation, and evaluation, and to the structural constraints encountered and the mitigation strategies developed in response. A qualitative case study design was employed. Three key informants were purposively selected: the school principal, the BOS Fund treasurer, and the vice-principal for facilities and infrastructure. Data were collected through semi-structured in depth interviews, non-participant observation, and document analysis between January and April 2026. Thematic analysis followed the Miles, Huberman, Saldaña interactive model; trustworthiness was established through source and technique triangulation, member checking, and a complete audit trail. Findings reveal that the school implemented budgeting through the School Activity and Budget Plan (RKAS), grounded in needs analysis, school quality reports, and prioritization meetings involving all units. Implementation followed the BOS Technical Guidelines under principles of transparency and accountability. Evaluation comprised periodic monitoring, accountability reporting, and internal and external audits confirming alignment between planning, expenditure, and regulatory requirements. Four structural constraints were identified: limited funding source diversity, delayed BOS disbursement, increasing infrastructure demand, and policy changes mitigated through priority adjustment, fund optimization, and stakeholder coordination. The study contributes to the literature on educational financing by providing an integrated identification of structural constraints in the budgeting process alongside strategic management recommendations a combination underrepresented in prior research on private school financial management.